Sensory History and Sociology — Offering a Helping Hand? - Angela Loxham (19, 2014)
Interdisciplinarity has been the focus of much attention across the social sciences and humanities in recent years. In this spirit, the article shows how sociology might be applied to sensory history and how to choose and apply suitable theories to this field. This is supported by a short discussion of the author's own research.